ANALISIS HUKUM MENGENAI PERLINDUNGAN SATWA LANGKA MENURUT CONVENTION ON INTERNATIONAL TRADE OF ENDANGERED SPESIES - Deppa Ringgi; Suarni. S (Fakultas Hukum Univesitas Kristen Indonesia Paulus, 2023)
Abstract Local communities benefit very little from the wildlife trade, because of the huge profits earned by the merchant. The research aimed at analyzing and comprehending CITES application in the endangered species protection effort, the supporting and inhibiting factors which affected CITES in the endangered species protection effort. The research used the normative legal method concerning the legal principles either in internasional of national law regarding CITES application in the endangered species protection. To find out the supporting and inhibiting factors which affected CITES concerning the endangered species protection, a series of interviews were carried out with the Ministry of Forestry, General Directorate of Forest Protection and Natural Conservation, Centre for Natural Resource Conservation, South Sulawesi in Makassar. The research result indicates that (1) CITES application on the endangered species protection has been firmly regulated in CITES convention 1973 and Acts Number 5 Year 1990. CITES frame work and mechanism are systematically used shared by 183 countries to organize and monitor the species trade, (2) there are several factors affecting CITES in the endangered species protection namely, inadequate legal vonverage, ineffective institutional role, economy, community’s culture, and land function transfer. Key words: Legal analysis, endangered species protection, CITES